Awareness and Perceived Barriers About Breast Cancer Screening and Breast Self Examination Amongst the Female Healthcare Workers at a Secondary Care Hospital in Saudi Arabia - Bin Abdul Aziz, Omer; Mughal, Muhammad Awais; Saad Alshelowi, Haila; Ahmad, Bilal; Al-Thobaithi, Naif Ali Rasheed; Hawsawi, Aysha Hamza Bakar (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess breast cancer screening and breast self examination awareness and perceived barriers amongst the female healthcare workers of a secondary care hospital in Saudi Arabia.Study Design: Cross Sectional Study.Place and Duration of Study: Qassim Armed Forces Hospital, Saudi Arabia, Jun 2023 to Aug 2023Methodology: A total of 68 workers participated in the study by non-probability convenience sampling. The data collection tool was a specially designed printed questionnaire consisting of demographic data, questions to assess awareness and perceived barriers regarding breast cancer screening and breast self examination.Results: Out of 68 HCWs, only 16(23.5%) healthcare workers had good knowledge about breast cancer risk factors, 22(32.4%) about signs and symptoms, 28(41.1%) about breast cancer screening and 9(13.2%) about breast self examination. The majority of the participants had fair knowledge in all categories. Breast self examination was the category with poorest scores. 29(42.6%) participants had poor knowledge about BSE. Certain barriers were identified to breast cancer screening that included embarrassment to exposure 38(55.8%), lack of awareness 35(51.47%) and family disapproval 26(38.2%). Perceived barriers to breast self examination included lack of knowledge 62(91.17%) and communication problems 60(88.2%) about breast issues.Conclusion: Although majority of healthcare workers had fair to good knowledge, there is a need to raise awareness about breast cancer screening. There is a lack of knowledge regarding breast self examination. Awareness campaigns are important to raise awareness amongst the healthcare workers and population in order to overcome perceived Barriers to breast cancer screening and self examination.